Antimicrobial susceptibility of Escherichia coli isolated from free range poultry or wild birds at the southern Caspian Sea coast of Iran - SEIFI, S.; SHIRZAD, M. R. (Journal of the Hellenic Veterinary Medical Society, 2017)
Objective of this study was the investigation of antimicrobial resistance of 95 Escherichia coli strains from faecal samples of wild birds and free range poultry in Mazandaran province (southern Caspian Sea coast of Iran), which were isolated during the period May to December 2012. Isolation rate was 59% or 30% from samples of free range poultry or wild birds, respectively. All isolates from free range poultry were susceptible to amikacin, danofloxacin, enrofloxacin, gentamicin, neomycin, whereas all were resistant to carbenicillin and erythromycin. In strains from wild birds, most common resistance was detected to be to carbenicillin and tetracycline. Multi-drug resistance was evident in all isolates from free range poultry and in 26% of those from wild birds. It is postulated that that wild birds may be infected by antibiotic resistant strains of E. coli and may serve as reservoirs of such strains.